Untangling Smart Cities : From Utopian Dreams to Innovation Systems for a Technology-Enabled Urban Sustainability /: From Utopian Dreams to Innovation Systems for a Technology-Enabled Urban Sustainability. (2019) - Unknown
No abstract available